2016
DOI: 10.1194/jlr.m064352
|View full text |Cite
|
Sign up to set email alerts
|

Tg6F ameliorates the increase in oxidized phospholipids in the jejunum of mice fed unsaturated LysoPC or WD

Abstract: This article is available online at http://www.jlr.orgOur laboratory, together with the University of California, San Diego group, pioneered the now widely accepted concept that oxidized phospholipids formed in the subendothelial space of the artery wall are responsible for initiating the early inflammatory response that is critical to the development of atherosclerosis (1-4). The recognition of oxidized phospholipids in the artery wall was established by using antibodies to oxidized phospholipids (5) and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…The decrease in oxidized phospholipids was associated with decreased inflammation in the jejunum and systemically42. We did not directly measure the level of the oxidized phospholipids formed in this study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The decrease in oxidized phospholipids was associated with decreased inflammation in the jejunum and systemically42. We did not directly measure the level of the oxidized phospholipids formed in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, Chattopadhyay et al 42 reported that feeding mice a concentrate of transgenic tomatoes expressing the apoA-I mimetic peptide 6F decreased the formation of oxidized phospholipids in the jejunum. The decrease in oxidized phospholipids was associated with decreased inflammation in the jejunum and systemically42.…”
Section: Discussionmentioning
confidence: 99%
“…Functional cholesterol homeostasis relies on the conversion of cholesterol into bile acids and is required to prevent the accumulation of cholesterol, triglycerides and toxic metabolites in organs such as the liver (Chiang ). Recently, the effect of LPC 18:1 on atherogenesis was demonstrated in a study wherein increased levels of intestinal and systemic inflammation were observed in Ldlr ‐null mice fed dietary LPC 18:1 (Chattopadhyay et al ). Autotoxins promote atherosclerosis by converting LPC 18:1 and other unsaturated LPCs into inflammatory and atherogenic LPAs (Navab et al ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that HDL assembled in areas of inflammation loses its anti‐inflammatory properties . Chattopadhyay et al . also demonstrated adding to the Western diet an apoA‐I mimetic peptide resembling 4F, Tg6F, dramatically suppressed oxidized phospholipid production and the related intense inflammatory response in the villus.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of immune cells surrounds the lymphatics and capillary tuft in the lamina propria. Chattopadhyay et al 28 fed mice a Western diet, and found oxidized phospholipids were formed in the lamina propria and provoked an intense inflammatory response in this area of the villus. It is known that HDL assembled in areas of inflammation loses its anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%